Studi Kelayakan Lokasi Budidaya Pembenihan di Desa Buko Poso, Mesuji, Lampung - Wildan Nurussalam; Kukuh Nirmala; Retnosari Retnosari (Jurnal Akuakultur Sungai dan Danau, 2023)
Buko Poso Village located in Way Serdang District, Mesuji Regency has a fairly good quantity and quality of water, but this potential has not been utilized for aquaculture activities. The purpose of this study is to analyze the feasibility of the location in Buko Poso Village, Mesuji, Lampung as a location for aquaculture activities. Field observation activities include direct (in situ) and indirect (ex situ) water quality measurements at four different locations, soil sampling, mapping using GPS and drones, market price surveys. Topographic map depicts Buko Poso Village included in the lowland area with a research area of 4.9 ha. The results of data analysis on water quality using the scoring method show that Buko Poso Village tends to be in class S3 (slightly appropriate), meaning that it has serious limiting factors so that to improve water quality, special treatment is needed. The soil condition in Buko Poso Village is mostly clay textured. Commodities that are suitable for cultivation include baung fish, jelawat fish, belida fish, snakehead fish, and tilapia which have a fairly high economic value.